EKSKLUSIVITAS PENDIDIKAN AGAMA ISLAM DAN ANCAMAN TERHADAP TOLERANSI - Siti Maqfirah (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This article explores the phenomenon of exclusivity in Islamic Religious Education (IRE) in various educational institutions across Indonesia and its impact on declining tolerance within a multicultural society. The study is motivated by the growing tendency to deliver religious content in a narrow, dogmatic manner that often limits dialogue with other belief groups. Utilizing a qualitative approach through literature review and curriculum policy analysis, this research examines the content of IRE teaching materials and student attitudes toward diversity. The findings indicate that the IRE curriculum, which lacks space for inclusive and pluralistic perspectives, tends to reinforce a "us versus them" narrative and fosters exclusive attitudes that contribute to social polarization. These findings are supported by case studies in religion-based schools, where students show limited readiness to interact with individuals of different faiths. In this context, teachers play a crucial role in shaping students’ religious reasoning; however, the lack of training on tolerance issues further amplifies exclusivity. This article proposes solutions including IRE curriculum reform based on interfaith dialogue and teacher training that emphasizes values of moderation and multiculturalism. The study concludes that it is essential to reconstruct IRE from an exclusive to an inclusive model to promote social harmony and prevent fragmentation in Indonesia’s plural society. Policy recommendations include the integration of tolerance materials into the curriculum and strengthening collaboration between the Ministry of Religious Affairs, Ministry of Education, and civil society organizations in overseeing religious education.